15x-11=-3

Simple and best practice solution for 15x-11=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15x-11=-3 equation:



15x-11=-3
We move all terms to the left:
15x-11-(-3)=0
We add all the numbers together, and all the variables
15x-8=0
We move all terms containing x to the left, all other terms to the right
15x=8
x=8/15
x=8/15

See similar equations:

| 0.2x=8.26 | | 0.4x+0.42=0.4x+0.62 | | 8=0.05b | | 4=t/4.5 | | 2(a-3)=180 | | x2-6x+1=3x+5/2 | | 0.2y=3 | | 2y+4=y+43 | | 4u–6=3u | | 2z-34=z+26 | | 35,000-2x=0 | | 2c-28=c+44 | | 4x2-1=35 | | 2c+4=c+46 | | x+x-9+2x=83 | | 475-s=164 | | 610(t)=16t^2 | | 5x(x+5)=40x+5(x^2+11) | | 489=118+7n | | 2u-46=u+45 | | 1=f/29-3 | | 16d-46=226 | | 2z-50=z+50 | | 57+x+x=907 | | z-535=288 | | 5(-3x+2)+(x-3)=-4(4x+5)+13 | | k/6=10 | | 0.25=0.75+r | | 2v-50=v+49 | | 37=6y+1 | | 7^x+5=4 | | 5(-3x+2)+(x-3)=-4(4x+5) |

Equations solver categories